Dealing with conflict at the workplace by adopting blake and mouton strategies / Ilyani Azer ... [et al.] - Azer, Ilyani; Mohamad, Siti Aishah; Ramli, Nurul Najwatul Huda; Ahmad Zaidi, Nurul Adilah (2013)
Conflict is an opposing interaction that interferes with the aims of another party (Almost, 2005). Singleton et at. (2011) stated; conflict is functional when the results are positive and people with dissent ideas intend their disagreement to have positive results. Blake and Mouton (1964) classified the five methods in managing interpersonal conflicts which is forcing, withdrawing, smoothing, compromising, and problem solving. In order to minimize the conflicts at workplace, the most suitable conflicts resolution will be the best techniques to face the situation. This has been conducted on a sample of 30 employees from Bank Simpanan Nasional (BSN) and Malayan Banking Berhad (Maybank) in Kuala Lumpur. The data obtained by the survey method with the measurement of 5 point Likert Scale and analyzed by several statistical method that was descriptive, frequency, compute variable and independent-sample test. The problem solving method had been chose by the employees in selecting their way of dealing the conflict.